20 Cells involved in SLE: beyond B cells. (6th April 2022) - Davidson, Anne
Abstract : Lupus nephritis (LN) is a common manifestation of systemic lupus erythematosus (SLE) that can lead to irreversible renal impairment. Lupus nephritis is initiated by the deposition of nucleic acid-containing material in the glomeruli, which triggers the engagement of complement, the activation of renal stromal cells and the recruitment of circulating pro-inflammatory cells. Disease progression is associated with tubulointerstitial hypoxia, metabolic dysfunction of the tubular epithelium, tubulointerstitial capillary rarefaction, accumulation of mixed lymphoid infiltrates and fibrosis. Each of these abnormalities may require different therapeutic approaches. In addition, loss of renal homeostatic programs contributes to morbidity including anemia, hypertension and increased cardiovascular risk. Forty percent of patients with moderate to severe renal lymphoid infiltrates progress to end stage renal disease over 2–5 years. 1 Immune infiltrates in LN kidneys can occupy several niches. Glomerular infiltrates consist mainly of macrophages, with T cells present in the more severe crescentic forms. Glomerular macrophages are recruited from the pool of circulating monocytes and include both classical and non-classical subtypes. Endothelial cells that are activated via nucleic acid-sensing toll-like receptors (TLRs) such as TLR 7 preferentially recruit non-classical monocytes. Macrophages change their phenotype upon glomerular entry and take on a phagocytic phenotype that is associated with disease activity. Mixed tubulointerstitial leukocyte infiltrates, sometimes with features of lymphoid organisation, are found in LN, particularly in chronic disease. B cell and T cell clones are present in LN tissue, and T peripheral helper cells that express high amounts of inducible T-cell costimulator and interleukin (IL)-21 are located next to B cells in the renal infiltrates. Lupus nephritis kidneys also contain large numbers of CD8 T cells and natural killer cells that produce interferon (IFN)γ. 2 Interestingly a predominance of B cells over T cells is associated with a better prognosis. The presence of antigen presenting cells such as myeloid dendritic cells (DCs) and plasmacytoid DCs, is associated with more advanced disease in LN. 3 In addition to infiltrating cells, the kidneys have a network of tissue resident macrophages located around glomeruli and in the tubular interstitium that are involved in immune surveillance. Peritubular renal macrophages are particularly susceptible to immune complex-mediated activation owing to their anatomic location near to small peritubular vessels that lack an intervening basement membrane. 4 These cells expand and become both inflammatory and pro-fibrotic during LN, suggesting a dysregulated repair process. 5 Overall, many types of immune cell are found in the kidneys of individuals with LN. 2 A better understanding how each infiltrating cell type contributes to renal injury is now needed so that pathogenic cells can be targeted, whereas those involved in organ protection and repair can be spared. References: Hsieh C, et al . Predicting outcomes of lupus nephritis with tubulointerstitial inflammation and scarring. Arthritis Care Res (Hoboken) 2011 Jun;63 (6):865–74. Arazi A, et al. The immune cell landscape in kidneys of patients with lupus nephritis. Nat Immunol 2019 Jul;20 (7):902–914. Kassianos AJ, et al. Increased tubulointerstitial recruitment of human CD141(hi) CLEC9A(+) and CD1c(+) myeloid dendritic cell subsets in renal fibrosis and chronic kidney disease. Am J Physiol Renal Physiol 2013 Nov 15;305 (10):F1391–401. Stamatiades EG, et al . Immune monitoring of trans-endothelial transport by kidney-resident macrophages. Cell 2016 Aug 11;166 (4):991–1003. Berthier CC, et al . Cross-species transcriptional network analysis defines shared inflammatory responses in murine and human lupus nephritis. J Immunol 2012 Jul 15;189 (2):988–1001. Learning Objectives: Describe the heterogeneity of immune cells in lupus nephritis kidneys Discuss the spatial organization of immune cells in lupus nephritis kidneys Explain the characteristics and functions of renal myeloid cells in lupus nephritis